Sex differences in and neural activity of fixed-interval and fixed-time interventions to promote self-control - Panfil, Kelsey (Kansas State University, 2023)
Impulsive behavior is associated with many maladaptive behaviors and diseases, which manifest and affect females and males differently. Because neuroscience research is often conducted in male subjects only, the mechanisms for these differences are unclear. The current study examined the effects of two abbreviated time-based interventions in female and male rats to further understand how these interventions may alter impulsive behavior both at behavioral and neurobiological levels. In the current study, male and female rats were randomly assigned to one of four conditions: FI (fixed-interval) intervention with FI choice task (FI-Exp), FT (fixed-time) intervention with FT choice task (FT-Exp), no training control with FI choice task (FI-Con), and no training control with FT choice task (FT-Con). In the Exp (experimental) conditions, rats received training on 10- and 30-s delays over the course of six sessions, and rats in the Con (control) groups did not receive any training but experienced the same environmental stimuli as Exp groups. After the intervention phase, all rats completed an impulsive choice task with corresponding response-initiated FI or FT contingencies. The FI schedule delivered during the intervention and/or choice task required a lever press to make a choice and a second lever press after the delay elapsed to receive food. The FT schedule required a lever press to make a choice but no further responses were required to receive food. Following the impulsive choice phase, rats were euthanized and perfused, and brains were processed for c-Fos, a marker of neural activity, in two prefrontal cortical brain regions and three subregions of the striatum. During the intervention and impulsive choice tasks, rats that received the FI schedules increased lever pressing in anticipation of food rewards. Rats that received the FT schedules did not enter the food cup in anticipation of food rewards but interacted with the levers often even though no response was required to receive food rewards. Rats in the Exp groups made more LL choices than the Con groups when the delay to reward was 0 s, but there were no differences between schedule or sex. In addition, all conditions showed similar sensitivity to delay in the choice task. Analyses of c-Fos showed that females had higher levels of c-Fos than males in all brain regions. We also found that rats in the Exp groups had higher levels of c-Fos in the dorsomedial striatum, dorsocentral striatum, and prelimbic cortex, and rats that received the FI schedule showed higher levels of c-Fos in the dorsomedial striatum, dorsocentral striatum, dorsolateral striatum, and prelimbic cortex. Based on the group, schedule, and sex effects in neurobiology, it is possible that time-based interventions are effective in both sexes but through different cognitive mechanisms that rely on a complex network of multiple brain regions. Time-based interventions may primarily decrease impulsive action in males and improve interval timing ability in females, both of which result in enhanced self-control. However, while multiple brain regions showed differential activity based on conditions, these differences did not strongly relate with behavioral measures. The current study produced relatively weak intervention effects, which could be due to the limited number of training sessions, the female estrous cycle’s effects on learning, and/or lever availability during the FT schedule. In the current study, the lever remained in the chamber until the delay elapsed and food was delivered whereas previous studies retracted the lever after the delay was initiated. Altogether, lever availability during the FT schedule may have affected delay sensitivity in a way that promoted temporal attention, but impaired interval timing ability compared to rats that received the FI schedule. The current study offers a variety of avenues for future research to further probe the cognitive and neurobiological mechanisms of time-based interventions for females and males.
Keywords: Impulsive choice; Interval timing; Sex differences; Time-based intervention; Rats; Self-control